ANALYSIS OF PRODUCTION FACTORS IN SOYBEAN FARMING IN DELI SERDANG REGENCY (CASE STUDY OF THE UPSUS PAJALE PROGRAM) - Siska Yulianita Lubis; Syahriandi Akbari; Irshad Ahmad Reshi (CV. Radja Publika, 2024)
This study aims to analyze the influence of production factors on soybean farming results in Deli Serdang Regency within the framework of the Special Effort Program (Upsus) PAJALE. The production factors analyzed include land area, seeds, fertilizers, labor, and pesticides. The research method used is a quantitative approach with Cobb-Douglas production function analysis using cross-section data of 90 farmer respondents. The results of the study indicate that partially the variables of land area, seeds, and fertilizers have a positive and significant effect on soybean production, while labor and pesticides have a positive but insignificant effect. Simultaneously, all independent variables have a significant effect on soybean production with an F count of 61.150 and a significance level of 0.000. The coefficient of determination (Adjusted R²) of 0.772 indicates that 77.2% of the variation in soybean production can be explained by production factors in the model, while the rest is influenced by other factors outside the study. The results of the technical efficiency analysis indicate that the use of land area, seeds, and pesticides is still in an inefficient condition (increasing returns to scale), so there is still potential for improvement. Meanwhile, fertilizer and labor use are inefficient (decreasing returns to scale), necessitating adjustments. Therefore, increasing soybean production in Deli Serdang Regency depends not only on additional inputs but also on efficient management of production factors and support from the Upsus PAJALE program.